Estimation of diffusion coefficients by intersecting different types of diffusion paths in a multi-principal element alloy. (1st January 2023) - Dash, Anuj; Paul, Aloke
Abstract: A unique method for estimating all types of diffusion coefficients in a multicomponent system is proposed by intersecting only two but different types of diffusion paths. This concept circumvents the limitations of the recently proposed diffusion couple methods, such as pseudo-binary, pseudo-ternary, and the body diagonal method, when practiced individually. Here the diffusion coefficients of all the elements can be estimated as compared to the estimation of diffusivities associated with only two or three elements which develop the diffusion profiles following the pseudo-binary and pseudo-ternary methods, respectively. This also reduces the laborious effort required to bring all the serpentine body diagonal diffusion paths close to each other to estimate the diffusivities with an unknown uncertainty when they do not intersect exactly. On the other hand, as proposed in this study, a serpentine conventional (or body diagonal) diffusion path can be intersected by a rectilinear pseudo-binary diffusion path with relative ease at a specific composition. The modification of the equation schemes for the application of different types of diffusion paths in the estimation of tracer, intrinsic, and interdiffusion coefficients is explained in detail. This method is demonstrated in a model NiCoFeCr multi-principal element system at a composition very close to the equiatomic composition. The influence of the vacancy wind effect on intrinsic and interdiffusion coefficients is described in detail. Graphical abstract: Image, graphical abstract